Probiotics in Pregnancy: Are Probiotics Preventative Against Infantile and Childhood Atopic Dermatitis? - Qureshi, Muhammad; Ismayilova, Miya; Lee, Justin; Lao, Jeffrey (Université d'Ottawa | University of Ottawa, 2016)
Background: Atopic dermatitis (AD), also known as atopic eczema, affects 3.5% of the global population5. Peak prevalence of AD occurs during infancy. No cure exists but certain preventative measures, such as probiotic use, have been proposed. Probiotic preventative treatments for AD most commonly involve Lactobacillus and Bifidobacterium strains. Objective: To comprehensively analyze the impact of prenatal and postnatal maternal probiotic supplements on the prevention of infantile and childhood atopic dermatitis. Methods: A structured literature review was conducted through the University of Ottawa Search+ database using the following keywords: probiotic, pregnancy, atopic dermatitis. Search+ was employed for its collection of databases available. Only peer-reviewed articles published from 2006 to 2016 were considered for the literature review. Results were filtered by terms in the inclusion and exclusion criteria. The search produced 82 publications from which 10 were eligible for the literature review. Results: Out of the 10 publications reviewed, 4 were RCTs and the remaining were systematic reviews and meta-analyses on mostly RCTs. 1 RCT did not discover a preventative effect from probiotic supplements in pregnancy on infantile and childhood atopic dermatitis. The remaining 9 publications provided evidence towards a statistically significant relationship between probiotics during pregnancy and a reduced risk of AD. Conclusion: Little heterogeneity exists in the findings; however, a consensus has not been reached. More research is needed to ascertain a clear relationship.